Mitigating Technical Risks in School Construction Projects through a Risk Notification and Impact Estimation System - Del Castillo, Valeria (2025)
The construction of schools faces technical risks that, if not managed properly, can generate delays and cost overruns, negatively impacting beneficiary communities. Previous studies highlight that early and proactive management of these risks, combined with appropriate strategies, can improve project efficiency and results. However, the lack of systematic approaches and advanced tools remains a major obstacle. In this context, this article proposes a potential risk notification system based on the principles of the Project Management Body of Knowledge (PMBOK) Guide and the latest version of the New Engineering Contract (NEC4) to facilitate the early identification of said risks, the qualitative and quantitative evaluation of their impact, and better communication and collaboration between those involved in the project. The contribution of the system lies in its ability to structure technical risk management in a precise and collaborative manner to mitigate its possible impacts on project deadlines and costs.